2009
DOI: 10.1128/jcm.01403-09
|View full text |Cite
|
Sign up to set email alerts
|

Moraxella lacunata Septic Arthritis in a Patient with Lupus Nephritis

Abstract: Moraxella lacunata is a rare, usually commensal gram-negative rod most commonly associated with eye infections. We report a unique case of noniatrogenic M. lacunata bacteremia and septic knee arthritis in a patient with class III-IV lupus nephritis and speculate on the association between invasive Moraxella infection and renal impairment. CASE REPORTOn 5 December 2008, a 24-year-old woman with lupus nephritis presented at her routine nephrology appointment with a 1-week history of increasing edema, arthralgia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…It has also been suggested that independent of the immune status of the host, Moraxella spp. may be more invasive pathogens than previously thought (Piontek & Herrmann-Czylwik, 1993;Woodbury et al, 2009). While differences in colonization by S. aureus have been attributed to host factors such as host immunity, age, gender and/or environmental factors (García-Rodríguez & Fresnadillo Martínez, 2002), the data generated from these 100 anterior nares samples could not reveal any relationship between host factors and bacterial structure or colonization of a particular species.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…It has also been suggested that independent of the immune status of the host, Moraxella spp. may be more invasive pathogens than previously thought (Piontek & Herrmann-Czylwik, 1993;Woodbury et al, 2009). While differences in colonization by S. aureus have been attributed to host factors such as host immunity, age, gender and/or environmental factors (García-Rodríguez & Fresnadillo Martínez, 2002), the data generated from these 100 anterior nares samples could not reveal any relationship between host factors and bacterial structure or colonization of a particular species.…”
Section: Discussionmentioning
confidence: 73%
“…It has also been suggested that independent of the immune status of the host, Moraxella spp. may be more invasive pathogens than previously thought (Piontek & Herrmann‐Czylwik, ; Woodbury et al ., ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moraxella bovis causes infectious bovine keratoconjunctivitis, known as pinkeye, in cattle and has been found in the nasal passages of cattle [6, 22]. Moraxella lacunata can cause conjunctivitis, keratitis, endocarditis, and otolaryngitis in humans [5, 9, 13, 23], but is rarely found in animal cases [7, 24].…”
mentioning
confidence: 99%
“…In human, M. lacunata is normally found in the oral cavity, cranial respiratory tract, and conjunctiva [9, 11, 14]. It usually causes otitis, sinusitis, conjunctivitis, and pharyngitis in children and has been reported to cause keratitis, meningoencephalitis, skin and soft tissue infection, and systemic infections including endocarditis, septicemia, and septic arthritis in humans [3, 11, 13, 20, 23]. Furthermore, Moraxella spp.…”
mentioning
confidence: 99%